The moderating role of access to finance on the impact of entrepreneurial awareness on Nigerian SMEs’ performance. - Kabir, Shamsudeen; Ooi, Yeng Keat; Hassan, Haslinda (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2017)
This study aims at examining the moderating role of access to finance on the relationship between entrepreneurial awareness and SMEs performance in north-western Nigeria. Literature suggested many factors as determinants of SMEs performance. But, few studies have been attempted to consider the influence of entrepreneurial awareness on SME performance in Nigeria. These few studies came up with mixed findings. Hence, this study aims to fill up the gap that exists in the extant literature by employing quantitative survey method. Using 354 owner/managers of SMEs in Kano, Kaduna and Sokoto State in north-western Nigeria. PLS-SEM was used for data analysis. It was found that entrepreneurial awareness is positively related to SME performance and access to finance is negatively and significantly related to SME performance. Additionally, access to finance moderates the relationship between entrepreneurial awareness and SME performance. Implication of the finding and suggestion for future research were also discussed.